HUBUNGAN ANTARA MOTIVASI BELAJAR DAN KESALAHAN STRUKTUR KALIMAT DASAR PEMELAJAR BIPA DI CINTA BAHASA INDONESIAN LANGUAGE SCHOOL - Wulan D.S., Ni L. Pt. (LPPM IKIP PGRI Bali, 2019)
This research aimed to 1) identify and describe Cinta Bahasa language school?s BIPA students learning motivation. 2) identify and describe the basic sentences structure?s error in the text made by BIPA students in Cinta Bahasa Language School. 3) identify and describe the relationship between learning motivation and basic sentences structure?s error in the text made by BIPA students in Cinta Bahasa Indonesian Language School. This research used qualitative descriptive proposal research. The subject of this research was BIPA student in Cinta Bahasa Indonesian Language School. The method used in collecting data was questionnaire and test. The result shown that (1) the highest statement that motivated the student was statement no. 1 with 98% percentage. Then, statement no. 14 got the lowest percentage with 34,7 %, (2) S-P-Ket structure got the highest percentage in error occurrence with 35 errors or 25,9%, there was only 1 error or 0,74%  in S-P-Ket-Pel , S-P-O-Ket-Pel, P-S-P, P-S-Ket, Ket-P-S, K-S-P, S-P-K-K sentence structures, (3)  29 students in statement no. 1 with 41% error, 21 students in statement no.16 with 52 % error.